Optimizing green routes for agro-tourism: insights from Samut Songkhram Province, Thailand - Rumpapak Luekveerawattana (Cogent Social Sciences)
Agricultural tourism, often termed agro-tourism, has emerged as a promising niche in the tourism industry, offering unique experiences for travelers while promoting sustainable rural development. This study investigates the factors influencing the optimization of green routes for agro-tourists in Samut Songkhram Province, Thailand. Through a quantitative approach, data were collected from 400 tourists who had visited agricultural destinations in the province. Structural equation modeling (SEM) was employed to analyze the relationships between key variables, including values of agriculture and culture, travel safety, accommodation quality, participation in activities, management of conservation of tourist attractions, and the potential of proximity to main tourist attractions. The findings reveal significant positive relationships between these variables, highlighting the importance of effective management practices in enhancing the agro-tourism experience. Recommendations for optimizing green routes for agro-tourists are discussed, emphasizing the need for collaborative efforts among stakeholders to promote sustainable agricultural tourism development in the region. Overall, this study contributes to the growing body of literature on agricultural tourism management and provides insights for policymakers, destination managers, and practitioners seeking to leverage the potential of agro-tourism for economic and environmental benefits.